Quality characteristics and antioxidant activities of mung bean starch gel containing eggplant (Solarium melongena L.) peel powder - Zhang, Yangyang; Song, Ka-Young; O, Hyeonbin; Kim, Young-Soon (Progress in Nutrition, 2017)
Eggplant is a good source of dietary fiber, minerals, and vitamins and has been reported to show antibacterial, anticancer, and antitumor effects. Eggplant peel is richer in the antioxidant anthocyanin than is its flesh. In this study, mung bean starch gels containing different concentrations of freeze-dried eggplant peel powder (EPP) – control (0% EPP), EPP1 (1% EPP), EPP3 (3% EPP), EPP5 (5% EPP), and EPP7 (7% EPP) – were prepared to examine their quality characteristics and antioxidant activities. The pH significantly decreased with increasing content of EPP, and EPP7 showed the lowest pH value (4.94). With the addition of EPP, L (lightness) decreased, while a (redness) and b (yellowness) increased. In texture analysis, hardness and chewiness of the mung bean starch gels decreased as the EPP content increased, while the springiness and fracturability did not significantly differ between control and other starch gels containing EPP. Syneresis increased during the storage period. On the 5th day, syneresis of EPP7 was the lowest (13.49%), while that of the control was the highest (17.37%). Total polyphenol and flavonoid contents, 2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) radical, and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities significantly increased with increments in the content of EPP. In sensory evaluation, using a 7-point scaling method, EPP5 showed the highest sensory preference scores in color, flavor, springiness, and overall acceptability. The results of this study suggest that mung bean starch gel prepared with 5% EPP is the most suitable product based on its quality characteristics and antioxidant activity.